Forensic dentistry methods to estimate the chronological age of individuals: a topic review - Catalina Pilar Ugalde-Barahona; José Manuel Olivares; Ernesto González-Mallea; Gustavo Moncada-Cortés; Osmir B. De Oliveira-Junior (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: global mobilization has created new needs. From sporting events to criminal matters, determining the chronological age of individuals is being used by forensic surgeons worldwide. The objective of the present study was to analyze the forensic methods to estimate the age of individuals, including the advantages and limitations of these methods. Method: a search was conducted in the Sistema de Bibliotecas de la Universidad Mayor (SIBUM): Dentistry & Oral Sciences Source, ClinicalKey, and Science Direct Freedom Collection, selecting papers published from 1980 to 2014. A manual search was also conducted, including specific journals and texts in this field, with no limitation as to the year of publication. The inclusion criteria were research projects aimed at determining the chronological age of individuals through forensic analysis of oral tissues. All published texts in a language other than English were excluded. In total, 70 publications were analyzed. Technological advances have paved the way for the study of new parameters; however, the original ones identified by Gustafson in 1950 are still studied. Conclusions: most studied methods are invasive in some degree. In addition, none of these techniques is accurate in its own; therefore, the combination of different measurement techniques is recommended, opening a field of research on techniques that are less invasive and can be a complement to the existing ones. Finally, the available information lead to conclude that research on populations of African and Asian descent is lacking, which is a current challenge because of globalization, migration, and the heterogeneity of current populations.